Majmū'a-yi āthār-i Ḥusām al-Dīn-i Khūʾī - Khūʾī, Ḥusām al-Dīn, (Miras Maktoob, ISBN: 9789004365452., 2019)
In every age and culture, royal courts have always attracted a multitude of scholars, artists and other folk seeking patronage and protection. In the Islamic world, one of these courts was that of the emirs of the Saljuqs of Rūm in Kastamonu in northern Anatolia. In the year 680/1282, Quṭb al-Dīn Shīrāzī (d. 709-1309), a student of Naṣīr al-Dīn Ṭūsī (d. 672/1274) who lived in Anatolia for years, dedicated his Ikhtiyārāt to the emir of Kastamonu, Muẓaffar al-Dīn Yavlaq Arslan (d. 691/1292). This same Muẓaffar also had a secretary in his service by the name of Ḥusām al-Dīn Khūʾī (alive in 709/1309-10), a refugee from Khūy near Tabriz in Iran. Ḥusām al-Dīn is the author of a number of works, six of which are published here for the very first time: four manuals on the art of the secretary, one Arabic-Persian glossary for use at the chancellery, and finally a collection of his poetry.